If Not Now, When? : Energy Price Reform in Arab Countries; April 2017 Rabat, Morocco. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2017)
Regulating energy prices has been a common practice around the world. The objective is, generally, to facilitate access to energy products, which are central to people's well-being and countries' economic development. However, energy price regulation also leads to wasteful and excessive consumption, discourages investment in the energy sector, and locks in inefficient technologies. Low energy prices also result in subsidies that erode fiscal space, while benefits for the poor are limited. All these effects have been evident in Arab countries, where domestic energy prices are among the lowest in the world. The current environment of low oil prices offers a unique opportunity for change. Lessons from international experience suggest how well thought-out and sequenced reforms can be successful.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet